A study of the relationship between negative and positive automatic thoughts and student’s life satisfaction among Malaysian undergraduate students - Mok, Joshua Lun Hua (2021)
In recent years, life satisfaction among undergraduates has gained scholarly attention and students who experienced low levels of life satisfaction may lead to depression. This study aims to investigate the relationship between negative and positive automatic thoughts, coping skills and students’ life satisfaction among undergraduate students in Malaysia. Using purposive sampling method, a cross-sectional study was conducted among 139 participants across Malaysia through online survey. There were less male (n=59, 42.2%) than female (n=80, 57.6%) The instruments used were ATQ-8 Automatic Thought Questionnaire (ATQ), Automatic Thought Questionnaire-Revised Positive (ATQ-RP), Brief COPE Inventory (BCI), and Satisfaction with Life Scale (SWLS). Findings reported that negative automatic thought was negatively correlated with life satisfaction where positive automatic thoughts was positively related to life satisfaction. On the other hand, adaptive coping was found to be correlated with life satisfaction. However, there was no correlation between maladaptive coping and life satisfaction. Only negative automatic thoughts (negatively), positive automatic thoughts (positively) and adaptive coping (positively) were found to predict life satisfaction. This research could be further explored with different variables to investigate the potential factors contributing to life satisfaction among undergraduate students in Malaysia context.